Vibrational Spectra of β″-Type BEDT-TTF Salts: Relationship between Conducting Property, Time-Averaged Site Charge and Inter-Molecular Distance - Takashi Yamamoto (Crystals, 2012)
The relationship between the conducting behavior and the degree of charge fluctuation in the β″-type BEDT-TTF salts is reviewed from the standpoints of vibrational spectroscopy and crystal structure. A group of β″-type ET salts demonstrates the best model compounds for achieving the above relationship because the two-dimensional structure is simple and great diversity in conducting behavior is realized under ambient pressure. After describing the requirement for the model compound, the methodology for analyzing the results of the vibrational spectra is presented. Vibrational spectroscopy provides the time-averaged molecular charge, the charge distribution in the two-dimensional layer, and the inter-molecular interactions, etc. The experimental results applied to 2/3-filled and 3/4-filled β″-type ET salts are reported. These experimental results suggest that the conducting property, the difference in the time-averaged molecular charges between the ionic and neutral-like sites, the alternation in the inter-molecular distances and the energy levels in the charge distributions are relevant to one another. The difference in the time-averaged molecular charges, ∆ρ, is a useful criterion for indicating conducting behavior. All superconductors presented in this review are characterized as small but finite ∆ρ.